Exodus and emancipation : Biblical and African-American slavery - Chelst, Kenneth (Urim Publications, 2014)
Presenting a new perspective on the saga of the enslavement of the Jewish people and their departure from Egypt, this study compares the Jewish experience with that of African-American slaves in the United States, as well as the latter group's subsequent fight for dignity and equality. This consideration dives deeply into the biblical narrative, using classical and modern commentaries to explore the social, psychological, religious, and philosophical dimensions of the slave experience and mentality. It draws on slave narratives, published letters, eyewitness accounts, and recorded interviews w.